PENGARUH FLASH SALE, DISCOUNT DAN TAGLINE “GRATIS ONGKIR” TERHADAP PERILAKU IMPULSIVE BUYING PENGGUNA SHOPEE DI SOLORAYA - Feni Desy Fitriana; Budi Istiyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to measure the influence of Flash Sales, Discounts and the Tagline "Free Shipping" on Impulsive Buying with the Shopee user population in Soloraya. Sampling used non-probability sampling and used a purposive sampling method with a sample size of 130 respondents. . Data collection uses a questionnaire with a Likert scale. This research applies several data tests, namely data instrument tests, classical assumption tests and multiple linear regression. The results of the t test state that the Flash Sale and Discount variables have an insignificant influence on Impulsive Buying, while the tagline "Free Shipping" has a significant influence on Impulsive Buying.